Family-Centered Care at Pediatric Cardiac Intensive Care Units in Germany and the Relationship With Parent and Infant Well-Being: A Study Protocol - Hannah Ferentzi; Ralph C. A. Rippe; Jos M. Latour; Stephan Schubert; Alona Girch; Alona Girch; Michaela Jönebratt Stocker; Michaela Jönebratt Stocker; Constanze Pfitzer; Constanze Pfitzer; Constanze Pfitzer; Joachim Photiadis; et al. (Frontiers Media S.A., 2021)
Rationale and Aim: Infants with Congenital Heart Disease (CHD) are at risk for neurodevelopmental delays, emotional, social and behavioral difficulties. Hospitalization early in life and associated stressors may contribute to these challenges. Family-centered Care (FCC) is a health care approach that is respectful of and responsive to the needs and values of a family and has shown to be effective in improving health outcomes of premature infants, as well as the mental well-being of their parents. However, there is limited empirical data available on FCC practices in pediatric cardiology and associations with parent and infant outcomes.Methods and Analysis: In this cross-sectional study, we will explore FCC practices at two pediatric cardiac intensive care units in Germany, assess parent satisfaction with FCC, and investigate associations with parental mental well-being and parenting stress, as well as infant physical and mental well-being. We will collect data of 280 infants with CHD and their families. Data will be analyzed using multivariate statistics and multilevel modeling.Implications and Dissemination: The study protocol was approved by the medical ethics committees of both partner sites and registered with the German registry for clinical trials (NR DRKS00023964). This study serves as a first step to investigate FCC practices in a pediatric cardiology setting, providing insight into the relationship between FCC and parent and infant outcomes in a population of infants with CHD. Results will be disseminated in peer-reviewed journals.